Improving Efficiency and Reducing Costs in Construction Inventory Management Using RAD Methodology - Alvalent, Derrell; Sihombing, Denny Jean Cross (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This research investigates the application of the Rapid Application Development (RAD) methodology in enhancing inventory management practices within construction companies. The study emphasizes the importance of stakeholder collaboration in defining clear project objectives and ensuring alignment with the company's operational needs. Through comprehensive data modeling, key data entities were accurately identified and structured, supporting effective inventory control. The process modeling phase demonstrated significant improvements in operational workflows by automating key processes, thereby reducing order processing time and enhancing efficiency. The RAD approach facilitated the rapid development of a functional prototype, enabling continuous user feedback and iterative refinement. The final application significantly improved inventory accuracy, reduced material wastage by 10%, and increased procurement efficiency by 20%. The successful implementation and refinement of the application, including data migration, system integration, and user training, validated the effectiveness of the RAD methodology. This research provides valuable insights into the potential of RAD to develop tailored inventory management solutions for construction companies, leading to improved efficiency and cost-effectiveness.